A trans‐European perspective on how artists can support teachers, parents and carers to engage with young people in the creative arts. (6th May 2022) - Dobson, Tom; Stephenson, Lisa
Abstract: Whilst the link between young people's well‐being and the creative arts is strengthening, there is a lack of research which focuses on the roles that artists play to help teachers and parents engage young people in the creative arts. This paper explores the benefits of and barriers to artists working in education in six European countries (England, Iceland, Germany, Greece, Italy and Austria). Using the '5A's model of creativity' and a view of professional development taking place within 'landscapes of practice', the data were analysed in order to explain how creativity is operationalised in the different contexts. Our study highlights the need for policy at a national and transnational level to value the creative arts in order to help teachers cross boundaries and utilise the full potential of the creative arts in schools. Our study also highlights that further research is needed into how artists shape teaching and curriculum and how schools engage parents in the creative arts in order to build an evidence‐base relating to young people's positive mental health that can affect policy at these levels.